Waterfront Brownfield Transformation into a Public Space (Proceedings of Faculty of Civil Engineering, 2023)
The City of Bakar has transformed part of its waterfront which until recently was used exclusively for industrial purposes. Intervention resulted in a modernly designed public space. Although it seems that there are no comparable features with a developed and large city like New York, this paper will present two case studies that prove the opposite. The aim of the paper is to present the comparison and results of two waterfront brownfield transformations. The research includes methods of transforming waterfront areas in such a way that they become accessible to citizens and significantly improve the residents' life and urban space quality. The paper presents the application of certain methods during planning, designing, and landscaping, as well as the comparative results of different scales of coastal transformation.
Keywords: waterfront; public park; brownfield transformation